The Relationship between Health Promotion and Smoking Behavior of Health Workers at Langsa Hospital - Elfida Elfida; Eva Sulistiany; Afnina Afnina (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research was motivated by the phenomenon that there are still many health workers who smoke their work environment, namely at Langsa Hospital even though health promotion has been carried out. So they want to examine the relationship between health promotion and their smoking behavior. Health promotion consists of advocacy, social support, and community empowerment. This study involved 50 health workers at the hospital with accidental sampling techniques and using chi square analysis tools. The results of the study found a relationship between advocacy and social support with smoking behavior, while for community support there was no relationship. This is due to the cultural culture of Aceh and allows every family to smoke and this habit is passed on to posterity even though it has been educated through various means. Therefore, it is recommended that the management of Langsa Hospital promote activities more actively so that health workers do not smoke while working and are in the hospital itself and at home. It can even stop smoking.